PROFIL DAN PERSEPSI PARA PEDAGANG BURUNG TERHADAP PERDAGANGAN PERKICI PELANGI (Trichoglossus haematodus) DAN UPAYA PELESTARIANNYA - W. Widodo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
The Rainbow Lorikeet (Trichoglossus haematodus) has known one of the forest commodities non-wood’s, which found relative abundantly on trade. To know the appearance and perception of the bird traders towards their conservation efforts of the Rainbow Lorikeets, a survey was done on July 2004 in the Pramuka and Jatinegara bird markets (Jakarta). Questioner’s method was used in this survey with 30 numbers of systematical questions asked for 61 respondents in those bird markets. The profiles of the traders are shown that 80.3% trade birds only; 55.7% of them were average 31–40 years old; 49.2% be educated junior schools; 54.1% have traded for less 10 years and 62.3% of the traders income less than 500.000 rupiahs per month. By Q-square Test were results that 88.5% of the traders have agreed with the wildlife animal protected of a law, and 62.3% and 67.2% were not the same opinion to the goverment programes, namely: captivity and quota systems, respectively.